N-terminal domain regulates steroid activation of elephant shark glucocorticoid and mineralocorticoid receptors. Issue 210 (June 2021) - Katsu, Yoshinao; Shariful, Islam M.D.; Lin, Xiaozhi; Takagi, Wataru; Urushitani, Hiroshi; Kohno, Satomi; Hyodo, Susumu; Baker, Michael E.
Highlights: GR N-terminal domain activates elephant shark GR. GR N-terminal domain activates elephant shark MR. GR DNA-binding domain activates elephant shark GR. Abstract: Orthologs of human glucocorticoid receptor (GR) and human mineralocorticoid receptor (MR) first appear in cartilaginous fishes. Subsequently, the MR and GR diverged to respond to different steroids: the MR to aldosterone and the GR to cortisol and corticosterone. We report that cortisol, corticosterone and aldosterone activate full-length elephant shark GR, and progesterone, which activates elephant shark MR, does not activate elephant shark GR. However, progesterone inhibits steroid binding to elephant shark GR, but not to human GR. Together, this indicates partial functional divergence of elephant shark GR from the MR. Deletion of the N-terminal domain (NTD) from elephant shark GR (truncated GR) reduced the response to corticosteroids, while truncated and full-length elephant shark MR had similar responses to corticosteroids. Swapping of NTDs of elephant shark GR and MR yielded an elephant shark MR chimera with full-length GR-like increased activation by corticosteroids and progesterone compared to full-length elephant shark MR. Elephant shark MR NTD fused to GR DBD + LBD had similar activation as full-length MR, indicating that the MR NTD lacked GR-like NTD activity. We propose that NTD activation of human GR evolved early in GR divergence from the MR.